1990
DOI: 10.1063/1.345567
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Mn on the grain-boundary potential barrier characteristics of donor-doped BaTiO3 ceramics

Abstract: Two compositions of BaTiO3 positive temperature coefficient of resistance ceramics, prepared identically except for the fact that a small addition of Mn (0.04 at. %) was made to one of them, were studied. The samples were sintered simultaneously in air at 1400 °C for 1 h and then annealed at 1200 ° for 5 h, using a muffle furnace. Room-temperature dielectric measurements in the audio- and radio-frequency ranges confirmed that Mn has a negligible effect on the bulk resistance. Arrhenius plots of resistivity vs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…Illingsworth et al 7 observed a similar increase from 2.3 to 2.5 as the Mn content was raised from 0 to 0.04 at.%. Thus the observed differences in our samples could be explained by localised small changes in Mn concentration due, for example, to incomplete mixing on this scale during powder preparation.…”
Section: Mesoscale Measurementssupporting
confidence: 49%
See 1 more Smart Citation
“…Illingsworth et al 7 observed a similar increase from 2.3 to 2.5 as the Mn content was raised from 0 to 0.04 at.%. Thus the observed differences in our samples could be explained by localised small changes in Mn concentration due, for example, to incomplete mixing on this scale during powder preparation.…”
Section: Mesoscale Measurementssupporting
confidence: 49%
“…[2][3][4] Acceptors such as Mn increase the height of the grain boundary barrier by activating deep trap states. [4][5][6][7] Isovalent substitutions of Pb or Sr for Ba are used to adjust T C 8 or are added in 'balancing' amounts to modify performance whilst maintaining T C . 9 Ca has little influence on T C , but is often also added as a grain refiner.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in sintering temperature of BBKT10-ASTMn would presumably improve T C by reducing evaporation of volatile elements. Moreover, the increase in q max /q min by 0.6 6 0.1 and 1.9 6 0.1 orders of magnitude by AST and ASTMn additions, respectively, for both BBKT5 and BBKT10, similar to BT-based PTC ceramics, 19 can be attributed to grain boundary segregation of impurities, 1 Al 31 (20) and Mn 21 (18) acceptors, in the presence of AST.…”
Section: Resultsmentioning
confidence: 93%
“…For the PTCR studies, the key role of manganese in PTCR ceramics is to modify the grain boundary layer characteristics while keeping the grain-bulk conductive; a small addition of 0.04 at. % of manganese can result in increasing the height of the grain boundary potential barriers by *40 % in the temperature range between T C and T max [23]. In this study, the manganese was added at the first stage into BaCO 3 and TiO 2 and then calcined.…”
Section: Introductionmentioning
confidence: 99%
“…Microstructure and electrical properties of Mn-doped BaTiO 3 have been extensively studied by numerous researchers [3][4][5][6][7][8][9][10][11][12][13][14][15]. For the donor-doped positive temperature coefficient of resistance (PTCR) ceramics, manganese depresses the grain size and enhances the electrical resistivity near the Curie temperature of BaTiO 3 [16][17][18][19][20][21][22][23]. For the based-metal-electrode (BME) MLCCs, undoped-perovskite BaTiO 3 materials are reduced and become semiconductors when fired in the protective atmosphere which is to prevent the internal electrodes from being oxidized.…”
Section: Introductionmentioning
confidence: 99%